72 PHASE II ADJUVANT CANCER-SPECIFIC VACCINE THERAPY FOR ESOPHAGEAL CANCER PATIENTS CURATIVELY RESECTED AFTER PREOPERATIVE THERAPY WITH PATHOLOGICALLY POSITIVE NODES. (17th September 2021) - Yasuda, Takushi; Nishiki, Kohei; Hiraki, Yoko; Kato, Hiroaki; Iwama, Mitsuru; Shiraishi, Osamu; Yasuda, Atsushi; Shinkai, Masayuki; Kimura, Yutaka; Sukegawa, Yasushi; Chiba, Yasutaka; Imano, Motohiro; et al.
Abstract: : Esophageal squamous cell carcinoma (ESCC) patients with pathologically positive nodes have a high risk for postoperative recurrence, despite curative resection after preoperative therapy. Subclinical micrometastases are an appropriate target for cancer vaccine. To elucidate the efficacy of adjuvant vaccine monotherapy using three HLA-A*24-restricted tumor-specific peptide antigens for ESCC, up-regulated lung cancer 10, cell division cycle associated 1 and KH domain-containing protein overexpressed in cancer 1, we conducted an exploratory prospective phase II clinical trial (UMIN000003557). Methods: Patients with ESCC who underwent curative resection after preoperative therapy and were found pathologically positive lymph node metastasis were enrolled from December 2009 to September 2014 and allocated into the control and vaccine groups (CG and VG) based on the HLA-A*2402 positive or negative. One mg each of three epitope peptides mixed with 1 mL of Montanide ISA 51 VG was administered the first 10weekly injections followed by 10 additional biweekly injections to VG. No other adjuvant therapy was given until recurrence occurred. The primary endpoint was relapse-free survival (RFS) and the secondary endpoint was esophageal cancer-specific survival (ECSS). Results: Thirty were in the CG and 33 in the VG. No significant difference was observed in RFS between the CG and VG (5-year RFS: 32.5% vs. 45.3%, p = 0.205 (one-sided)), but the recurrence rate significantly decreased with the number of peptides which induced antigen-specific cytotoxic T lymphocytes. The VG showed a significantly higher 5-year ECSS than the CG (60.0% vs. 32.4%, p = 0.045 (one-sided)) probably due to the better clinical responses in patients of the VG to the post-recurrence therapy and this difference was more prominent in patients with CD8+ and programmed death-ligand 1 double negative tumor (68.0% vs. 17.7%, p = 0.010 (two-sided)). Conclusion: Our results suggested that the cancer peptide vaccine suppressed the postoperative recurrence, enhanced the post-recurrence therapy and improved the survival of ESCC patients, particularly in the cases without CD8 infiltration and PD-L1 expression. A phase III randomized controlled study has been conducted in response to these results, and the results are waiting to be published.